A protocol for the development of a validated scale of household water insecurity in the United States: HWISE-USA - Amber L. Pearson; Wendy Jepson; Alexandra Brewis; Jeremiah Osborne-Gowey; Amber Wutich; Melissa Beresford; Asher Y. Rosinger; Adam M. Enders; Justin Stoler (PLoS ONE, 2025)
Background New metrics of household water insecurity have been validated for low- to middle-income countries, but it is unclear how these measurements apply to the experiences of people living in high-income countries. This project aims to develop and validate a novel metric for household water insecurity experiences in the United States (HWISE-USA) using a cross-sectional design and data from the Southwest, Midwest, and Western regions. Methods We outline the protocol for the development and validation of a novel household water insecurity scale for the United States to address this scientific need, including the following key steps: (1) item development through literature and theory; (2) pre-testing of items and expert review; (3) scale development and item reduction; and (4) scale validation. To assess the performance of the HWISE-USA scale, we will follow the same scale development analytics on a separate, quasi-nationally-representative U.S. sample. The scale will be generated from household survey data collected from communities at risk of water insecurity throughout the United States. Discussion We explain how a novel metric of water insecurity experiences for households in the United States has important implications for resource allocation, structural interventions, public health and infrastructure planning, and reductions in inequalities. Registration osf.io/zvqs4